Religious Moderation Education Management: An Analysis of Inclusivity Values with A Behavioristic Approach in Islamic Boarding Schools - Maulidiyya Najwa Balqis Azzahro; M Rikza Chamami; Nur Asiyah; Nasikhin Nasikhin (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to uncover, analyze, and reflect on the application of religious moderation education management based on a behavioristic approach at the Fathimah Al-Amin Progressive Islamic Boarding School, Semarang. Using qualitative case study methods and triangulation techniques (in-depth interviews, participatory observations, documentation), this study identifies three main forms of the application of behavioristic habituation approaches through structured daily routines, positive reinforcement in the form of symbolic and material appreciation of moderate behavior, and modeling by authoritative figures (coaches) who consistently show tolerant and inclusive attitudes. The value of inclusivity was found to be internalized through three dimensions: curricular (integration of diversity themes in the yellow book and contemporary discussions), social (non-discriminatory policies in daily interactions), and participatory (students' deliberations in internal decision-making). However, its implementation faces three main challenges: cultural resistance from students and families who view inclusivity as a threat to the purity of faith, limited capacity of teachers to integrate behavioristic principles reflexively without being trapped in repressive disciplines, as well as external ideological pressures and epistemological shifts of the student generation that demand rational justification for habituation. Theoretically, this research makes an important contribution by showing that behavioristic approaches that are often criticized as rigid or technocratic can actually be an effective instrument in instilling religious moderation when contextualized in the Islamic value of rahmatan lil 'alamin and combined with a reflective-dialogical approach. In practical terms, these findings offer an alternative model for salaf Islamic boarding schools to reform their education systems without sacrificing traditional roots, while enriching the religious education literature based on empirical and contextual evidence.